Indonesian Archipelagic Ipseities: Beyond Human Rights and Dichotomies of Personhood - Hamzić, Vanja (2011)
This talk presents a brief legal anthropological account of the narratives and politics of representation of various human subjectivities in Indonesia who transgress the dominant universalising sexual and gender norms. It traces both macro- and micro-streams of regulation, including those reliant on liberal legalistic discourse of human rights, whose extremities produce the stringent ‘heteronormative’ versus ‘homonormative’ poles – the two mutually reinforcing otherworlds bereft of the intrinsic complexity of sexual/gender experience across the country’s archipelagic and islandic selves.